2008
DOI: 10.1002/pbc.21730
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical features of the JAK2 V617F mutation in pediatric patients with sporadic essential thrombocythemia

Abstract: These findings suggest that the JAK2 V617F mutation is not rare in childhood sporadic ET cases, and that these cases might be older and myeloproliferative features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The acquired JAK2 V617F mutation, resulting in constitutive activation of tyrosine kinases in the absence of cytokines, is present in around 50–60% of adult ET patients (Baxter et al , ). Varying frequencies of the JAK2 V617F mutation have been reported in childhood ET, ranging from 0% to 50%, lower than or similar to that in adults (Randi et al , ; El‐Moneim et al , ; Teofili et al , ,b; Nakatani et al , ; Veselovska et al , ; Giona et al , ; Ismael et al , ) (Table ). The variability can probably be ascribed to the heterogeneity of each cohort, as remarkably different frequencies have been detected using the same method to identify the JAK2 mutation (Randi et al , ; Teofili et al , ; Giona et al , ).…”
Section: Molecular Features and Clonal Evolutionmentioning
confidence: 98%
See 1 more Smart Citation
“…The acquired JAK2 V617F mutation, resulting in constitutive activation of tyrosine kinases in the absence of cytokines, is present in around 50–60% of adult ET patients (Baxter et al , ). Varying frequencies of the JAK2 V617F mutation have been reported in childhood ET, ranging from 0% to 50%, lower than or similar to that in adults (Randi et al , ; El‐Moneim et al , ; Teofili et al , ,b; Nakatani et al , ; Veselovska et al , ; Giona et al , ; Ismael et al , ) (Table ). The variability can probably be ascribed to the heterogeneity of each cohort, as remarkably different frequencies have been detected using the same method to identify the JAK2 mutation (Randi et al , ; Teofili et al , ; Giona et al , ).…”
Section: Molecular Features and Clonal Evolutionmentioning
confidence: 98%
“…Children diagnosed with ET are reported to have a lower risk of vascular events than adults. The rate of thrombotic events in children is 0-11Á1%, and major bleeding events are rarely seen (Yang & Qian, 2000;Randi et al, 2006;Teofili et al, 2007aTeofili et al, , 2009Nakatani et al, 2008;Veselovska et al, 2008;Giona et al, 2012) (Table I). After a long period of follow-up, Teofili et al (2007aTeofili et al ( , 2009 reported that the risk of thrombotic events from two paediatric ET cohorts was 0/18 (0%) and 1/13 (7Á7%), respectively, both much lower than that of adult patients (31%).…”
Section: Clinical Manifestation and Complicationsmentioning
confidence: 99%
“…Diagnosis of ET in children may require exclusion of hereditary manifestations transmitted as hereditary character, involving genetic defects of thrombopoietin receptor, thrombopoietin and MPL mutations expressed in both somatic and germ line cells. 7 Primary myelofibrosis The proposed 2008 WHO criteria for PMF are applicable in children and young adults. Bone marrow histology is essential to exclude secondary causes of myelofibrosis (neoplastic and non-neoplastic) and the prefibrotic phase of PMF that presents a different natural history in comparison with true ET.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
“…One small study showed that 3 of 6 pediatric ET patients harbored a JAK2V617F mutation, but all had increased PRV-1 expression. 62 A larger study showed a significantly decreased frequency of JAK2V617F mutation in pediatric patients compared to adults. It also showed a significantly lower degree of clonality in the pediatric patients.…”
mentioning
confidence: 97%